PENGARUH VARIASI MASSA STEARIN DAN MINYAK JELANTAH HASIL PENJERNIHAN DENGAN KARBON AKTIF TERHADAP KUALITAS LILIN: The Effect of Variations of Stearin Mass and Used Cooking Oil From Purification with Activated Carbon on the Quality of The Candle - Siti Jamilatun; Ikko Nirwana Luthfiani; Dita Permata Putri; Joko Pitoyo; Aster Rahayu (Universitas Darussalam Gontor, 2022)
Cooking oil is vegetable oil that has been purified and can be used as foodstuff. Consumption of cooking oil is used as a medium for frying foodstuff, to add flavor and to form texture in bread making. Cooking oil that has been used repeatedly or commonly known as used cooking oil has a very bad impact on our body and will pollute the environment if it is not managed properly. Candles are made of paraffin, melt easily when heated, and can be used as a light source. For making candles, a chemical is added, namely stearin. The function of this stearin is to give shape for candles because stearin will solidify once it cools. The presence of palmitic acid and stearic acid contained in stearin causes stearin to be in a solid state at room temperature. The study was conducted using 400 ml of used cooking oil which was then clarified with variations in the mass of activated carbon as much as 40, 80, and 120 grams. The clarified oil will then be analyzed for its absorbance value using a spectrophotometer UV/VIS, then it will become a wax with the addition of variations in the mass of stearin as much as 50, 75, and 100 grams. The resulting candle will be tested which includes hardness, organoleptic test, flame test, and flame resistance of the candle.